The Expanded SWEET Gene Family Following Whole Genome Triplication in Brassica rapa - Wei, Yanping (Genes (Basel), 2019)
The SWEET family, which includes transcripts of a cohort of plant hexose and sucrose transporters, is considered key to improving crop stress tolerance and yield through its role in manipulating the carbohydrate partitioning process. The functions and regulatory roles of this gene family are variable among different species; thus, to determine these roles, more species-specific information is needed. Brassica rapa displays complicated regulation after a whole-genome triplication (WGT) event, which provides enormous advantages for use in genetic studies, thus it is an ideal model for exploring the functional and regulatory roles of SWEETs from a genetic perspective. In this study, the results of a homology search and phylogenetic relationship analysis revealed the evolutionary footprint of SWEETs among different plant taxa, which showed that plant SWEETs may have originated from Clade II and then expanded from vascular plants. The amino acid sequence characteristics and an analysis of the exon-intron structure of BrSWEETs duplicates clarified that SWEETs retention occurred after a WGT event in B. rapa. An analysis of the transcriptional levels of BrSWEETs in different tissues identified the expression differences among duplicated co-orthologs. In addition, qRT-PCR indicated that the BrSWEETs’ co-orthologs were varied in their stress responses. This study greatly enriches our knowledge of SWEETs in the B. rapa species, which will contribute to future studies on the Brassica-specific regulatory pathways and to creating genetic innovations.